Scales for assessing therapeutic adherence and competence in dialectical behaviour therapy for PTSD: development and analysis of psychometric properties. Issue 1 (31st December 2022) - Steil, Regina; Müller-Engelmann, Meike; Stangier, Ulrich; Priebe, Kathlen; Fydrich, Thomas; Weiß, Judith; Dittmann, Clara
ABSTRACT: Background: The assessment of therapeutic adherence and competence is essential to understand mechanisms that contribute to treatment outcome. Nevertheless, their assessment is often neglected in psychotherapy research. Aims/Objective: To develop an adherence and a treatment-specific competence rating scale for Dialectical Behaviour Therapy for Posttraumatic Stress Disorder (DBT-PTSD), and to examine their psychometric properties. Global cognitive behavioural therapeutic competence and disorder-specific therapeutic competence were assessed using already existing scales to confirm their psychometric properties in our sample of patients with PTSD and emotion regulation difficulties. Method: Two rating scales were developed using an inductive procedure. 155 videotaped therapy sessions from a multicenter randomised controlled trial were rated by trained raters using these scales, 40 randomly chosen videotapes involving eleven therapists and fourteen patients were doubly rated by two raters. Results: Both the adherence scale (Patient-level ICC = .98; αs = .65; α p = .75) and the treatment-specific competence scale (Patient-level ICC = .98; αs = .78; α p = .82) for DBT-PTSD showed excellent interrater – and good reliability on the patient level. Content validity, including relevance and appropriateness of all items, was confirmed by experts in DBT-PTSD for the new treatment-specific competence scale. Conclusion: Our results indicate that both scales are reliable instruments. They will be useful to examine possible effects of adherence and treatment-specific competence on DBT-PTSD treatment outcome.